The Relationship Between Chaebol And Firm Value Using Bayesian Network - Sun, Eun-Jung; Park, Sung-Jin (Journal of Applied Business Research, 2017)
The purpose of this study is to analyze the effects of being a chaebol company, the biggest company characteristic variable, on firm value. It tries to overcome the limitation of multiple regression analysis mostly used in preceding research. That is, as multiple regression analysis assumes uniform linearity between dependent and independent variables, it could not reflect the diverse types of the real world. Thus, based on being a chaebol company and financial information, company characteristic variables influencing firm value, this study derives causal relationships existing between them. The results could help managers and various accounting information users in their decision-making by providing them with information of what company characteristics would directly or indirectly influence firm value. To this end, this study utilizes Bayesian Network and attempts Markov Blanket. In the end, all the analysis methods used in this study not only provides significant results, but also raises its practical value by offering information of diverse situations that could occur in the real world.